The Role of the Repository for the Preservation of Management Information and Digital Services in the Library of the Raden Intan Islamic University - Eni Amaliah; Rahmat Iqbal; Irva Yunita; Hildawati Almah (Insaniyat: Journal of Islam and Humanities, 2025)
The repository application is a tool used by librarians in preserving managed information and improving library digital services. Utilization evaluation is important in knowing the management of the repository. This is only to achieve one expectation, which is satisfaction for users. The purpose of this research is to ensure the use of the repository as a form of information preservation owned by the UIN Raden Intan library to make it easier for academics to take research information and to make it easier for students to conduct thesis research. The method used is qualitative descriptive. This method gives freedom to researchers to conduct research reviews so that researchers can deliver this research according to the conditions that occur. To support data collection, researchers used interview, observational and literature methods. The result of this study is that the UIN Raden Intan library stores information periodically with the aim of presenting information as needed. Repository information is presented using the format of year, study program and faculty. This provides convenience and flexibility for all UIN academics in taking digital information and services. The repository has been implemented using an online model, this adds flexibility for academics and researchers in obtaining research references without being hampered by distance and time in the UIN Raden Intan library.